A systematic review of systematic reviews on interventions for caregivers of people with chronic conditions. (16th September 2014) - Corry, Margarita; While, Alison; Neenan, Kathleen; Smith, Valerie
Abstract: Aim: To evaluate the effectiveness of interventions to support caregivers of people with selected chronic conditions. Background: Informal caregivers provide millions of care hours each week contributing to significant healthcare savings. Despite much research evaluating a range of interventions for caregivers, their impact remains unclear. Design: A systematic review of systematic reviews of interventions to support caregivers of people with selected chronic conditions. Data sources: The electronic databases of PubMed, CINAHL, British Nursing Index, PsycINFO, Social Science Index (January 1990–May 2014) and The Cochrane Library (Issue 6, June 2014), were searched using Medical Subject Heading and index term combinations of the keywords caregiver, systematic review, intervention and named chronic conditions. Review methods: Papers were included if they reported a systematic review of interventions for caregivers of people with chronic conditions. The methodological quality of the included reviews was independently assessed by two reviewers using R‐AMSTAR. Data were independently extracted by two reviewers using a pre‐designed data extraction form. Narrative synthesis of review findings was used to present the results. Results: Eight systematic reviews were included. There was evidence that education and support programme interventions improved caregiver quality of life. Information‐giving interventions improved caregiver knowledge for stroke caregivers. Conclusion: Education, support and information‐giving interventions warrant further investigation across caregiver groups. A large‐scale funded programme for caregiver research is required to ensure that studies are of high quality to inform service development across settings.